A.galanga (L.)-Willd Rhizome and O.sanctum L. Leave Essential Oils as Culex sp. Larvicide - Sugiarto Puradisastra; Regina Aurellia Limijaya; Angelica Rosa Septiana Hartono; Susy Tjahjani (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Culex sp. can transmit diseases such as encephalitis and filariasis which is a public health problem because of elephantiasis, disability, and a neglected tropical disease. To prevent these diseases, the mosquitoes need to be eradicated and larvicides are considered to control them at their early stage. Temephos, a synthetic larvicide, could cause several disadvantage, such as potential toxicity against non-target organisms and easierto-develop mosquito resistance. Botanical sources from Indonesian spices i.e. galangal (Alpinia galanga (L.) Willd.) and basil (Ocimum sanctum L.) are potentially used as larvicide. This study aimed to explore the larvicidal effect of their essential oils compared against temephos against Culex sp. A true experimental study was done using several concentrations and replications of these essential oils in each container, consisting of 25 third instar of Culex sp larvae for 24 hours at room temperature according to WHO procedure. The percentage of dead larvae was analyzed by ANOVA/ Kruskal Wallis. The study showed that Alpinia galanga ( L.) Willd. and Ocimum sanctum L. essential oils had larvicide activity and their activity starting from 140 ppm and 400 ppm consecutively was the same as temephos 1 ppm.